The Relationship Between Simple Renal Cysts and Renal Function in Patients With Type 2 Diabetes - Wei, Ling; Xiao, Ying; Xiong, Xiaofen; Li, Li; Yang, Yuan; Han, Yachun; Zhao, Hao; Yang, Ming; Sun, Lin (Frontiers in Physiology, 2020)
Introduction: Simple renal cysts (SRCs) are the most common acquired cystic kidney disease, but the relationship between SRCs and renal function has not been clarified in patients with type 2 diabetes mellitus (T2DM). Methods: A retrospective study was conducted to analyze the clinical features of renal cysts and ultrasound data of the kidney in 4304 patients with T2DM. Results: The prevalence of SRCs in patients with T2DM was 21.1%. Compared to patients with no SRCs, patients with SRCs had worse renal function (estimated glomerular filtration rate: 108.65±40.93 vs. 92.38±42.1 ml/min/1.73 m2, p<0.05). After adjusting the confounders, SRC was related to estimated glomerular filtration rate in patients with T2DM (odds ratio=1.49, 95% confidence interval (1.24, 1.79), P <0.01). Age, gout, proteinuria, cerebrovascular disease (CVD), and increased serum phosphorus levels were associated with SRCs in patients with T2DM. Conclusions: SRCs are associated with worse renal function in patients with T2DM. More attention should be paid to gout, proteinuria, CVD, serum phosphorus levels and renal function in T2DM patients with SRCs.